Aromatherapy in Stroke Patients: Is it Time to Begin? - Contrada, Marianna; Cerasa, Antonio; Tonin, Paolo; Bagetta, Giacinto; Scuteri, Damiana (Frontiers in Behavioral Neuroscience, 2021)
Stroke is the second largest cause of death worldwide, causing disease with long-term consequences and considerable healthcare costs. The application of new nursing interventions aimed at reducing distressing behaviors and at increasing patient comfort is an important part of the care and, until now, there are no defined guidelines. Aromatherapy has been demonstrated to be efficient in several other neurological disorders for the treatment of somatic and emotional diseases and to promote patient health. In the management of stroke patients, the aromatherapy is still in its infancy. The first evidence coming from animal models demonstrated a consistent and reliable neuroprotective effect in reducing cerebral ischemia-reperfusion injury. In the last few years, some preliminary data being to be collected in humans revealed significant influence in reducing patients’ pain and emotional distress. In this perspective study, we sought to summarize, for the first time, the main findings emerging from this new field of study, discussing the future opportunities to be translated into primary care practice.